SAFETY AND THERAPEUTIC EFFECTS OF ORALLY ADMINISTERED AKST4290 IN NEWLY DIAGNOSED NEOVASCULAR AGE-RELATED MACULAR DEGENERATION. Issue 6 (June 2022) - Stewart, Michael W.; Garg, Seema; Newman, Erin M.; Jeffords, Elizabeth; Konopińska, Joanna; Jackson, Sam; Sikorski, Bartosz L.; Rawner, Esther S.
Abstract : Supplemental Digital Content is Available in the Text. In patients with treatment-naive neovascular age-related macular degeneration, 6 weeks of orally administered AKST4290 was well-tolerated and associated with improved best-corrected visual acuity scores. AKST4290 is being developed as a potential oral alternative for the treatment of neovascular age-related macular degeneration, and further studies are warranted. Abstract : Purpose: To evaluate the safety and therapeutic effects of orally administered AKST4290 (formerly BI 144807 and ALK4290) in treatment-naive patients with neovascular age-related macular degeneration. Methods: In this prospective, multicenter, open-label Phase 2a pilot clinical study, 30 patients with newly diagnosed neovascular age-related macular degeneration self-administered AKST4290 (400 mg) orally twice daily for 6 weeks. Patients were examined weekly for safety, to measure best-corrected visual acuity (BCVA), and to perform exploratory morphologic assessments. The primary endpoint was the mean change in BCVA from baseline to end of treatment, and the secondary endpoint was safety. Exploratory endpoints investigated potential changes in macular morphology. Results: Mean BCVA improved by +7.0 letters (95% CI, 2.2–11.7); 24 patients (82.8%) had stable or improved BCVA, with 6 (20.7%) gaining ≥15 letters. No patients experienced severe or serious adverse events. Conclusion: In this 6-week study, AKST4290 treatment was associated with improved BCVA scores in patients with treatment-naive neovascular age-related macular degeneration. All adverse events were mild or moderate in severity and no safety issues were identified. Treatment of neovascular age-related macular degeneration with AKST4290 warrants further investigation in randomized, placebo-controlled trials.